HUBUNGAN PENGETAHUAN KESEHATAN REPRODUKSI DAN PENDIDIKAN IBU DENGAN RISIKO WANITA PUS MUDA DI DESA CANDIGARON KECAMATAN SUMOWONO KABUPATEN SEMARANG TAHUN 2017 - Pratama, Thoriq Rizqy; Nugroho, Djoko; Dharminto, Dharminto (Fakultas Kesehatan Masyarakat, 2017)
The risk of young married woman is a woman who has been married for less than 20 years.Health impact is the risk of maternal death during childbirth.Factors of knowledge, education, culture become the cause. Every year there is a risk of young married women in Candigaron village, Sumowono district, Semarang regency for the last five years (2013-2017).The objective of the study was to analyze the relationship of reproductive health knowledge and maternal education with the risk of young married women.The type of research is explanatory research with case control study approach because the number of cases occur slightly.The case population is the first married woman with age less than 20 years.The control population is the first married woman with the age of 20-35 years(889 women).The sample case is the total population with 30 respondents.The control sample has the same number of cases (30 respondents).The total sample is 60 respondents.Data were analyzed by univariate and bivariate.Bivariate analysis was conducted with descriptive and analytic bivariate.Descriptive bivariate uses frequency distribution and analytic bivariate with chi square. The results of the study provide information that there is no correlation between reproductive health knowledge (p=0,071 OR 2,983 with 95% CI = 1,044-8,527) and no mother’s education relationship (p = 0,127 OR 3,250 with 95% CI=0,888-11,899) with risk of young married woman.Advice given to young women is to form PIK Remaja with the aim of delaying the first marriage age and for KUA by facilitating PIK Remaja and socializing marriage law and the impact of young marriage.